2008
DOI: 10.2527/jas.2007-0153
|View full text |Cite
|
Sign up to set email alerts
|

A regional evaluation of injections of high levels of vitamin A on reproductive performance of sows1,2

Abstract: A regional study involving 443 litters from 182 sows was conducted at 5 cooperating experiment stations to determine the effects of an i.m. injection of vitamin A at weaning and breeding on subsequent litter size of sows. Sows were assigned to 1 of 3 treatments given at weaning and again at breeding: 1) a placebo i.m. injection (2 mL of corn oil), 2) i.m. injection with 250,000 IU of vitamin A (1 mL of vitamin A palmitate in oil), and 3) i.m. injection with 500,000 IU of vitamin A (2 mL of vitamin A palmitate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The vitamin A requirement for optimal reproductive performance is age dependent and likely greater in younger sows. 12 Gilts that received adequate dietary vitamin A through nine months of age completed two reproductive cycles without vitamin A supplementation without developing deficiency symptoms, suggesting adequate vitamin A stores in the liver. 13,14 Moreover, mature sows without vitamin A supplementation required 4 parities before deficiency symptoms became evident.…”
Section: Discussionmentioning
confidence: 99%
“…The vitamin A requirement for optimal reproductive performance is age dependent and likely greater in younger sows. 12 Gilts that received adequate dietary vitamin A through nine months of age completed two reproductive cycles without vitamin A supplementation without developing deficiency symptoms, suggesting adequate vitamin A stores in the liver. 13,14 Moreover, mature sows without vitamin A supplementation required 4 parities before deficiency symptoms became evident.…”
Section: Discussionmentioning
confidence: 99%
“…Although none of the three participating universities possessed the animals and resources necessary to conduct the current experiment alone, combined data from over 120 farrowing events per treatment were adequate to detect significant differences for several response measures. Members of the multistate research committee of which the authors are members, have successfully used this strategy before ( Lindemann et al, 2004 , 2008 ; Carter et al, 2018 ). Animal and facility characteristics, and performance measures for the research sites employed in this study appear in Tables 1 and 3 .…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that injection or dietary supplementation of β-carotene during early gestation can enhance embryo survival, litter size and litter weight of piglets (9,20,21), but less information on its impact in late pregnancy has been obtained. However, in this study, dietary supplementation of β-carotene at late stage of pregnancy showed limited effect on the number of live birth and litter weight at parturition.…”
Section: Discussionmentioning
confidence: 99%